Hydrogels of Polycationic Acetohydrazone-Modified Phosphorus Dendrimers for Biomedical Applications: Gelation Studies and Nucleic Acid Loading - Evgeny K. Apartsin; Alina E. Grigoryeva; Audrey Malrin-Fournol; Elena I. Ryabchikova; Alya G. Venyaminova; Serge Mignani; Anne-Marie Caminade; Jean-Pierre Majoral (MDPI AG, 2018)
In this work, we report the assemblage of hydrogels from phosphorus dendrimers in the presence of biocompatible additives and the study of their interactions with nucleic acids. As precursors for hydrogels, phosphorus dendrimers of generations 1–3 based on the cyclotriphosphazene core and bearing ammonium or pyridinium acetohydrazones (Girard reagents) on the periphery have been synthesized. The gelation was done by the incubation of dendrimer solutions in water or phosphate-buffered saline in the presence of biocompatible additives (glucose, glycine or polyethylene glycol) to form physical gels. Physical properties of gels have been shown to depend on the gelation conditions. Transmission electron microscopy revealed structural units and well-developed network structures of the hydrogels. The hydrogels were shown to bind nucleic acids efficiently. In summary, hydrogels of phosphorus dendrimers represent a useful tool for biomedical applications.